Peripheral Neuropathy Due to Common Variable Immunodeficiency: Case Report and Narrative Review. (May 2019) - Long, Christopher P.; Suzuki, Hiroshi; Vitale, Kenneth
A 63-year-old woman with common variable immunodeficiency (CVID) presented with 1 year of insidious onset lower extremity pain and weakness. She underwent a circuitous workup, failed to improve despite treatment for various presumed diagnoses. She presented to a University physical medicine and rehabilitation clinic with continued symptoms. Electrophysiologic testing was recommended revealing a lower extremity motor greater than sensory axonal neuropathy. While CVID has known central nervous system complications, to our knowledge, this represents the second known reported case of peripheral neuropathy. We review the literature on CVID and summarize neurological disease mechanisms and manifestations. Although peripheral neuropathy is a rarely documented complication of CVID, providers need to be aware of potential peripheral nervous system complications of primary immune deficiencies such as CVID due to its significant impact on physical performance, balance, and fall risks.